Influence of seasonal variation on severity and outcomes in acute bronchiolitis - Saheb, Shaik Ateal; Reddy, R. Samba Siva (International Journal of Contemporary Pediatrics, 2017)
Background: Bronchiolitis is a predominant cause of respiratory insufficiency and hospitalization in infants during the first year of their life. Respiratory syncytial virus (RSV) has been the major causative virus; other viruses also cause bronchiolitis. Some are activated in winter while another virus in non-winter seasons. This seasonal trend affects the morbidity in infants. In the Indian context, data regarding seasonal influence on the severity and complications of acute bronchiolitis is less. Hence, this study was undertaken to assess the influence of season on morbidity on mortality in acute bronchiolitis. Methods: Infants or children <2 years of age, with the first episode of acute bronchiolitis diagnosed clinically, were evaluated. Clinical, demographic, radiological and risk factors were recorded and correlated with seasons. Results: The age of the infants was 4.0±2.9 months. Peak occurrence (87.7%) was within six months of age. 78/105 (74.3%) of bronchiolitis occurred during July to December. 22/105 (20.9%) were mild, 43/105 (43.9%) were moderate, and 40/105 (38.9%) were severe. The order of chest X-ray findings are consolidation <atelectasis <normal <pulmonary infiltrates <bilateral Hyperareation. Apnea was seen in 2.9%, Otitis media in 7.6% and seizures in 3.8% of infants. The season did not show statistically significant trend on the severity of bronchiolitis. There were no infant deaths due to bronchiolitis in the present study. Conclusions: In the present study, the season did not show statistically significant trend on the severity of bronchiolitis. Studies with more extensive population are needed to reassess the seasonal effects on morbidity of acute bronchiolitis.